(untitled) (Research, Society and Development, 2022)
Dietary restrictions imposed on patients with chronic kidney disease can make them susceptible to food monotony, thus, food and nutrition education actions must become permanent practices, as they contribute to the quality of life of patients, helping in the process of acceptance and acceptance. understanding of the new eating habits required by the disease and treatment. The objective of this article is to report experiences lived by undergraduate students of Nutrition when promoting food and nutrition education actions. This is a descriptive study, of the experience report type, about the experiences of students of the Nutrition course of the Faculty of Health Sciences of Trairi-UFRN, during the performance of Food and Nutrition Education actions with patients assisted in a Center of Nephrology in a city in Rio Grande do Norte. Three actions were carried out, two aimed at reducing the consumption of ready-made sugars and seasonings and another related to the preparation and distribution of a recipe booklet, aiming to contribute to the reduction of food monotony during social distancing. In the actions, the active participation of patients who were on hemodialysis was valued, with clarification of doubts about the topics addressed and others. EAN actions are strongly correlated with the treatment and health status of the patient. Therefore, they must be worked on continuously and permanently, and must be included in the routine care of hemodialysis centers, as they contribute to the promotion of food and nutrition autonomy. as a form of entertainment for patients, helping to improve their quality of life.